Sport Motivation Levels of Adolescent based on Demographic Status - Putri, Wulandari; Mukhlisin; Gumilang, Eva Sri (Indonesian Journal of Sport Management, 2025)
Participation in sports and physical activities plays a crucial role in promoting physical fitness and mental well-being among adolescents. However, motivation to engage in such activities often differs across demographic factors, particularly gender and residential background. This study aimed to analyze the differences in sport motivation levels among adolescents based on gender and residential status using the Self-Determination Theory framework. A cross-sectional study was conducted involving 501 students aged 17–21 years majoring in sport and health-related fields. The Sport Motivation Scale-II (SMS-II) was utilized to assess participants’ motivation levels. The Mann–Whitney U test was applied to examine differences between male and female students, as well as between those from rural and urban areas. Findings revealed a significant difference in sport motivation between male and female students, with males showing higher motivation levels. However, no significant difference was observed between students from rural and urban areas. The results indicate that gender remains an influential factor in shaping sport motivation among adolescents. Implementing gender-responsive strategies may enhance youth participation in sports and physical activities. Future studies should further investigate social and environmental factors influencing sport motivation to design inclusive and effective interventions.